2010
DOI: 10.1210/jc.2009-1796
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Secondary, Primary, and Compensated Hypogonadism in Aging Men: Evidence from the European Male Ageing Study

Abstract: Symptomatic elderly men considered to have LOH can be differentiated on the basis of endocrine and clinical features and predisposing risk factors. Secondary hypogonadism is associated with obesity and primary hypogonadism predominately with age. Compensated hypogonadism can be considered a distinct clinical state associated with aging. Classification of LOH into different categories by combining LH with T may improve the diagnosis and management of LOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
495
10
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 528 publications
(556 citation statements)
references
References 39 publications
41
495
10
10
Order By: Relevance
“…defined as normal/reduced blood testosterone in the face of elevated LH and thus, an altered LH to testosterone ratio (7,60). Because adult Leydig cells develop from the stem cells, this finding implies that the stem cells are modified functionally as well as numerically because of reduced fetal androgen exposure, and this ultimately translates in adulthood into compromised steroidogenesis.…”
Section: -Hsd3mentioning
confidence: 99%
See 2 more Smart Citations
“…defined as normal/reduced blood testosterone in the face of elevated LH and thus, an altered LH to testosterone ratio (7,60). Because adult Leydig cells develop from the stem cells, this finding implies that the stem cells are modified functionally as well as numerically because of reduced fetal androgen exposure, and this ultimately translates in adulthood into compromised steroidogenesis.…”
Section: -Hsd3mentioning
confidence: 99%
“…This suggested connection has widespread implications, because one in six young men in northern European countries has a low sperm count (<20 million/mL) (68), and testosterone levels in men of all ages are declining (4-6). Moreover, it has implications for morbidities associated with aging and the aging-related decline in testosterone levels (3,(7)(8)(9)69), because ∼10% of aging men exhibit compensated Leydig cell failure (7). Our findings also provide a pathway through which fetal growth/birth weight could influence testosterone levels in adult men (13), because no explanation for this association is currently available.…”
Section: -Hsd3mentioning
confidence: 99%
See 1 more Smart Citation
“…According to EMAS (172), total T concentrations <8 nmol/L (230 ng/ dL) confirms the diagnosis of LOH; if total T is between 8 and 11 nmol/L (230-320 ng/dL), free T <220 pmol/L (63.5 pg/mL) supports the diagnosis. A novel diagnostic entity is that of compensated hypogonadism, defined as low normal T (>10.4 nmol/L-300 mg/dL) and elevated LH concentrations (>9.4 IU/L) (173). Proper classification of LOH and exclusion of other causes of hypogonadism in the aging male is established through history, clinical evaluation (digital rectal examination) and additional laboratory (hematocrit (Ht), prostate-specific antigen (PSA), follicle-stimulating hormone (FSH), prolactin, SHBG, ferritin and drug screen) and imaging studies (pituitary MRI, bone densitometry), as needed.…”
Section: Late-onset Hypogonadismmentioning
confidence: 99%
“…While primary and compensated hypogonadism are a concomitant problem of aging, secondary hypogonadism may be correlated to obesity and such other, above-mentioned risk factors. 21 Studies evaluating the basis of age-dependent changes in T levels have identified pathophysiological dysfunctions to be central, at the hypothalamo-pituitary axis, 8 together with secondary changes in the testes, 22 In a step-wise pattern, hypothalamic dysfunction will lead to downregulation of the anterior pituitary and decline in the levels of gonadotropins and T. 8 In contrast to primary testicular failure due to gonadal pathology, the continued aromatisation to E 2 and the gonadotropin-suppressant effect of E 2 would modulate the ratio of free T to E 2 , 23,24 accompanied by further decrements in luteinizing hormone, follicle-stimulating hormone and T levels, 8 and contribute to the age-related alterations in E 2 /T ratio and the decline of serum T levels.…”
Section: Endogenous Cross-talk With Oestrogenmentioning
confidence: 99%